Charles Beaudouin : une histoire d'instruments scientifiques - Beaudouin, Denis (Sciences & histoire., 2005)
A book on the adventure of Charles Beaudouin, a builder of scientific instruments. This book takes us on a fascinating journey, choc-a-block with new discoveries, twists and turns not only scientific but also technological and financial as we revisit the extraordinary French scientific and industrial adventure of the 20th century.